2002
DOI: 10.1521/suli.32.2.158.24406
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Survivors' Perceptions of the Treating Clinician

Abstract: Seventy-one suicide survivors were surveyed about their perceptions of the clinicians who were treating their loved one at the time of death. Survivors provided information regarding their perceptions and attitudes toward clinician behaviors before and after the suicide and their perceptions of helpful and troubling aspects of clinician behaviors. Results indicated that survivors share a number of common opinions regarding the mental health care providers treating their loved ones. Several differences existed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Moreover, many clinicians fear blame and/or litigation from family members of the decedent (Campbell & Fahy, 2002; Gitlin, 2007; Hendin, Haas, Maltsberger, Szanto, & Rabinowicz, 2004; Hendin et al, 2000). To assess the validity of these fears, a recent survey of family members of suicide completers found that families who considered legal action rated the clinician as secretive, whereas families who did not consider lawsuits appreciated the clinician's personal expression of grief and felt that the clinician was more willing to answer questions about the treatment trajectory (Peterson, Luoma, & Dunne, 2002).…”
Section: Therapists Professional Responses To Suicidementioning
confidence: 99%
“…Moreover, many clinicians fear blame and/or litigation from family members of the decedent (Campbell & Fahy, 2002; Gitlin, 2007; Hendin, Haas, Maltsberger, Szanto, & Rabinowicz, 2004; Hendin et al, 2000). To assess the validity of these fears, a recent survey of family members of suicide completers found that families who considered legal action rated the clinician as secretive, whereas families who did not consider lawsuits appreciated the clinician's personal expression of grief and felt that the clinician was more willing to answer questions about the treatment trajectory (Peterson, Luoma, & Dunne, 2002).…”
Section: Therapists Professional Responses To Suicidementioning
confidence: 99%
“…Therefore, if the patient dies by suicide, it is widely seen as the fault of the therapist, rather than the fault of a disease (or, more pointedly, the fault of the patient). Indeed, one relevant survey conducted by Peterson, Luoma, and Dunne (2002) of family members who lost a loved one to suicide showed that the majority of the sample were inclined to contact an attorney to pursue malpractice wrongful death tort litigation against the mental health clinician who clinically cared for their loved one. Moreover, 25% of the sample reported that they actually did contact a lawyer to pursue litigation.…”
Section: Suicide As An Interpersonal Actmentioning
confidence: 99%
“…Data reveals that approximately 30,000 suicides occur in the United States every year (Hoyert, et al, 2001). Of these 30,000, approximately 6,000 patients are in treatment at the time of their death (Peterson et al, 2002). Among psychiatric inpatients, the rate of suicide has been estimated to be 5 to 30 times that of the general population: 370 per hundred thousand as opposed to ten to twelve per hundred thousand (Farberow 1981).…”
Section: Introductionmentioning
confidence: 99%